Application of Electrical Resistivity Imaging Technique in Slope Stability Study of Granitic Residual Soils in the Cameron Highlands, Pahang - Lau, Kien Liong (2005)
This thesis reports on the result of an empirical study to use electrical resistivity imaging technique in the assessment of ultimate shear strength (USS) and the dynamic cone penetration resistance (DCPR) of residual soil derived from the weathering product of granitic rock. The study also attempts to identify the depth and lateral extent of possible slip surface of sloping ground in Main Range Granite especially on the cut slope, bordering the federal road in Cameron Highlands. Soil samples were taken from the field and its petrophysical, electrical resistivity, USS and DCPR were studied in laboratory. In the field, electrical resistivity imaging (ERI) survey, USS and DCPR probing have also been carried out. The result of cross-correlation between USS and resistivity and the ERI- USS and DCPR from laboratory and field investigations were integrated to obtain relationships, which were applied to determine the USS and the DCPR of residual soil from the electrical resistivity inversion data obtained from the study area. The residual soil was derived from the weathering of Main Range granitic rock, Cameron Highlands. Soil classification results show that the soil in the study area comprised of mainly sandy soil. This study shows that the resistivity, x and the USS, y was related by an equation y = 2.81Ln(x) + 30.29. The DCPR is related to the USS by; DCPR = 0.07(USS) + 6.88. The present work is applicable for soil at moisture content between 6% and 30%. Result of field survey and 2-D subsurface ERI and subsequence translation of ERI into USS and DCPR also indicated that the depth of the sliding surface of the failed slopes were about 1 m – 1.5 m below ground surface. The boundary between the translated and intact soil was at the USS of about 200 kPa and DCPR value of 30 J cm-2 per 10 cm penetration. The present study have shown that it is possible to estimate the USS and DCPR of the residual soil and to predict the depth and lateral extent of the possible slip surface using electrical resistivity imaging survey at lower cost and wider coverage of survey area